Christology, controversy and community: New Testament essays in honour of David R. Catchpole - Horrell, David G.; Catchpole, David R.; Tuckett, Christopher M. (Novum Testamentum / Supplements, 2000)
This collection of essays by an international team of prominent New Testament scholars is in honour of David Catchpole, recently retired from his position as the Saint Luke's Foundation Professor of Theological Studies at the University of Exeter, UK. The essays represent a range of approaches and topics, connected together by a focus on various kinds of christological claim, whether by the historical Jesus, in the Q tradition, John, Paul or the synoptics, and their connection with controversy and the construction of early Christian community. The contributors are: Stephen Barton, Peder Borgen, Richard Burridge, Marinus de Jonge, James Dunn, Earle Ellis, Birger Gerhardsson, Michael Goulder, Morna Hooker, John Kloppenburg Verbin, Robert Morgan, John Painter, Ronald Piper, Peter Richardson, Christopher Rowland, Graham Stanton, N.T. Wright, and the editors.